Artesunate Reverses Clozapine-induced Lipid Metabolism Disorder in BRL-3A Cells by Effecting AMPK Pathway - Cui, Yali; Ling, Lingyun; Huang, Qingjun; Xu, Haiyun (Current Chinese Science, 2023)
Background: Clozapine (CLZ) is the only registered drug for treatment-resistant schizophrenia and also associated with metabolic abnormalities, including obesity, hyperglycemia, and dyslipidemia. Objective: This study aimed to examine the effects of CLZ on lipid metabolism in BRL-3A cells, measure possible effects of artesunate (ART) on the CLZ-induced alterations in lipid metabolism, and explore the molecular mechanism underlying the CLZ- and ART-induced changes in the cells. Methods: BRL-3A cells were cultured in DMEM at different conditions in the CLZ experiment (20, 30, or 40 μM CLZ), CLZ-ART experiment (40 μM CLZ followed by ART at 5, 10, or 20 μM), or CLZ-ART experiment consisting DMSO, CLZ, CLZ+ART, and ART groups. In addition to cell viability assessment, triglyceride, total and free cholesterol in BRL-3A cells were measured by biochemistry analyses, and levels of lipid metabolism-related genes and relevant proteins were evaluated by means of quantitative PCR and Western blot. Results: CLZ in the used range increased levels of free and total cholesterol in BRL-3A while upregulated mRNA levels of HMGCR, PPARα, and PPARγ. Moreover, the treatment increased SREBP-1c mRNA and protein levels in the cells, although it showed no impact on the phosphorylation of AMPK. ART treatment following CLZ exposure reversed the CLZ-induced high levels of free and total cholesterol in BRL-3A. ART effectively ameliorated or normalized the CLZ-induced changes in the HMGCR, PPARα, PPARγ, and SREBP-1c. Furthermore, ART increased AMPK phosphorylation in BRL-3A. Conclusion: These results suggest that ART exerts a cholesterol-lowering effect in BRL-3A by affecting the AMPK/SREBP-1c/PPARγ pathway.
Keywords: clozapine (CLZ)